Signatures of memory: brain coactivations during retrieval distinguish correct from incorrect recollection - Mendelsohn, Avi; Furman, Orit; Dudai, Yadin (Frontiers in Behavioral Neuroscience, 2010)
Are specific distributed coactivations in the brain during memory retrieval a signature of retrieval outcome? Here we show that this is indeed the case. Widespread brain networks were reported to be involved in the retrieval of long-term episodic memories. Although functional coactivation among particular regions occurs during episodic memory retrieval, it is unknown to what extent it contributes to the accuracy and confidence of recollection. In this study we set out to explore this question. Participants saw a narrative documentary movie. A week later they underwent an fMRI scan during which they either accepted or rejected factual or fictitious verbal statements concerning the movie. Correct vs. incorrect responses to factual statements were more common and were provided with higher confidence than those made to fictitious statements. Whereas activity in the retrieval network correlated mostly with confidence, coactivations primarily correlated with memory accuracy. Specifically, coactivations of left medial temporal lobe regions with temporal and parietal cortices were greater during correct responses to factual statements, but did not differ between responses to fictitious statements. We propose that network coactivations play a role in recovering memory traces that are relevant to online retrieval cues, culminating in distinct retrieval outcomes.